(untitled) (The Research of Medical Science Review, 2025)
Background: Intrauterine contraceptive devices (IUCDs) are widely recognized for their effectiveness in contraception, offering a reversible, long-term solution. Objective: This study aimed to compare the mean insertion pain experienced by women receiving intravenous analgesics versus placebo during IUCD insertion. Study Design and Setting: A randomized controlled trial was conducted at the Department of Obstetrics and Gynecology, Pakistan Air Force Hospital, Islamabad from 3 March 2025 to 6 June 2025. Methodology: A total of 300 females seeking IUCD insertion were randomly assigned to either the intravenous analgesic group (150 participants) or the placebo group (150 participants). Data on age, BMI, parity, and previous vaginal deliveries were collected. The insertion pain was assessed using a Visual Analog Scale (VAS), where scores ranged from 0 (no pain) to 10 (severe pain). The data were analyzed using SPSS version 25, and comparisons between groups were made using independent samples t-test, with p ≤ 0.05 considered significant. Results: The mean insertion pain score in the Intravenous group was significantly lower (3.09 ± 2.13) compared to the Placebo group (3.82 ± 2.45), with a p-value of 0.009. The analysis also showed that 43.3% of participants in the Intravenous group reported mild pain, while 32.0% in the Placebo group did. For moderate pain (4-7), 46.7% in the Intravenous group and 56.7% in the Placebo group experienced it, with a significant p-value of 0.023. Conclusion: Intravenous analgesics significantly reduced pain during IUCD insertion compared to placebo. The use of intravenous analgesia is recommended to improve patient comfort during the procedure. Further research in different settings could confirm these findings.